Model Pembelajaran PKN Berbasis Karakter Abad 21 untuk Meningkatkan Sikap Tanggung Jawab Siswa SD - Jayusman, Muhammad Idam Cahaya; Ramadhani, Davina Nathania; Rizki, Alifiyah; Wahyuni, Wahyuni; Hayati, Auliya Aenul (JPK (Jurnal Pancasila dan Kewarganegaraan), 2026)
This study aims to analyze the application of the 21st-century character-based Civic Education (PKN) learning model in fostering a sense of responsibility among elementary school students. A descriptive qualitative approach was used, with in-depth interviews conducted with classroom teachers, subject teachers, and the Principal at Sindang Laut Public Elementary School. The results show that character-based learning that integrates 4C skills (critical thinking, creativity, collaboration, communication) can increase students' moral awareness and social responsibility. Teachers act as facilitators of values through contextual, reflective, and collaborative activities such asocial projects and case-based discussions. Evaluation was conducted authentically by assessing changes in student behavior and engagement. The main obstacles, namely the lack of consistency in applying values outside of school and the influence of the digital environment, were overcome through collaboration with parents and the strengthening of school culture. This study emphasizes the importance of synergy between schools, families, and communities in shaping responsible character and recommends ongoing training for teachers to.